Social Media Use, Motivation and Mental Health Awareness: An Analysis of Nigerian Undergraduates - Ojewumi, Aderemi Kehinde; Oyeleke , Johnson Tunde; Ajibewa , Olusegun Dele; Adedayo , Olufunmilayo; Adeyemo , Olabisi Adedoyin (Jurnal Psikologi Teori dan Terapan, 2025)
Background: This study investigated the relationship between Social Media Use (SMU), Social Media Motivation (SMM), and Mental Health Awareness (MHA) among Nigerian undergraduate students. Objective: Grounded in Uses and Gratifications Theory, the research aimed to determine the individual and combined predictive roles of SMU and SMM on students’ awareness of mental health issues, while also examining gender differences in MHA. Method: A total of 294 participants were selected through multistage sampling from two federal universities in southwestern Nigeria. Standardized questionnaires were used to collect data, which were analyzed using Pearson correlation, multiple regression, and independent t-tests. Results: Findings revealed no significant relationship between SMU and MHA, while SMM showed a positive, significant correlation with MHA. SMU and SMM jointly predicted MHA, explaining 15% of the variance. Male students demonstrated significantly higher mental health awareness than females. Conclusion: These findings highlight the importance of motivational and gender-related factors in designing effective mental health awareness interventions. Future research should explore platform-specific and culturally informed longitudinal studies to enhance the generalizability and applicability of results. Abstrak Latar Belakang: Penelitian ini menyelidiki hubungan antara Penggunaan Media Sosial (SMU), Motivasi Media Sosial (SMM), dan Kesadaran Kesehatan Mental (MHA) di kalangan mahasiswa Nigeria. Tujuan: Didasarkan Teori Penggunaan dan Kepuasan, penelitian bertujuan untuk menentukan peran prediktif individu dan gabungan dari SMU dan SMM terhadap kesadaran mahasiswa akan masalah kesehatan mental, sementara juga memeriksa perbedaan gender dalam MHA. Metode: Sebanyak 294 partisipan dipilih melalui pengambilan sampel bertingkat dari dua universitas federal di barat daya Nigeria. Kuesioner terstandarisasi digunakan untuk mengumpulkan data, yang kemudian dianalisis menggunakan korelasi Pearson, regresi berganda, dan uji-t independen. Hasil: Temuan menunjukkan tidak ada hubungan signifikan antara SMU dan MHA, sementara SMM menunjukkan korelasi positif dan signifikan dengan MHA. SMU dan SMM bersama-sama memprediksi MHA, menjelaskan 15% dari varians. Siswa laki-laki menunjukkan kesadaran akan kesehatan mental lebih tinggi secara signifikan daripada perempuan. Kesimpulan: Temuan menyoroti pentingnya faktor motivasi dan faktor yang berhubungan dengan gender dalam merancang intervensi kesadaran kesehatan mental yang efektif. Penelitian di masa depan harus mengeksplorasi studi longitudinal yang spesifik pada platform dan berdasarkan budaya untuk meningkatkan generalisasi dan penerapan hasil.